ANALISIS SISTEM DAN PROSEDUR AKUNTANSI PELUNASAN GADAI PADA PT PEGADAIAN CABANG WATAMPONE - Dahlia, Dahlia; Harisa, Muh; Mustadir, Mustadir (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2024)
PT Pegadaian is a state-owned company which operates in the field of pawn credit distribution. A pledge is a right obtained by a creditor over a movable item given to him by the debtor in his name to guarantee a debt. In pawning there is an accounting system for granting and paying off pawns. The accounting system plays an important role in the company's internal control system. The purpose of this research is to determine the accounting system and procedures for pawn repayment at PT Pegadaian Watampone Branch. The data collection techniques used were observation, interviews, literature study and documentation. Meanwhile, the data analysis method used in this research is qualitative descriptive analysis. Based on the results of the discussion relating to the problem formulation in this research, the pawn settlement accounting system and procedures at PT Pegadaian Watampone Branch are generally running well because they are in accordance with the pawn repayment SOP that has been implemented by the pawnshop, starting from paying off the pawn until handing over. receive pawned goods. The pawn repayment accounting system and procedures at PT Pegadaian Watampone Branch are also supported by the implementation of internal control quite well, this is evident from the documents and credit records used by PT Pegadaian in the pawn repayment accounting systems and procedures used has been adequate.